Exposure of aquatic organisms to natural radionuclides in irrigation drains, Qena, Egypt - K. Salahel Din; N. K. Ahmed; A. Abbady; F. M. Abdallah (Scientific Reports, 2023)
Abstract Natural radioactivity in irrigation drains was measured by gamma spectrometry, and the resulting dose rates received by aquatic organisms were estimated. Irrigation water and sediment samples were collected from 5 irrigation drains located in Qena governorate, south of Egypt. The average activity concentrations (Bq L−1) of 226Ra, 232Th, and 40 K in irrigation water were 0.76 ± 0.06, 0.27 ± 0.02, and 8.14 ± 0.71, while in sediment (Bq kg−1) were 24.46 ± 1.84, 20.72 ± 1.45, and 453.00 ± 28.14, respectively. The total dose rate per aquatic organism ranged from 1.94 × 10–04 µGy h−1 in Mollusc to 7.15 × 10–04 µGy h−1 in phytoplankton. These values are far from the international recommended limit 400 µGy h−1 for chronic exposure to aquatic organisms, and the dose rate screening value of 10 µGy h−1 suggested by ERICA tool. Based on these results, it is unlikely that harmful effects will appear on the considered aquatic organisms due to exposure to natural radioactivity in the studied environment.